Domain and perception on community resilience: comparison between two countries - Irasanti, Siska Nia; Respati, Titik; Januarita, Ratna; Yuniarti, Yuniarti; Chen, Hana Wei Jun; Marzo, Roy Rillera (Frontiers in Public Health, 2023)
The COVID-19 outbreak demonstrates how unprepared the world is for a different type of crisis, especially non-physical calamities. Revitalizing community involvement in disaster management is essential for making a community resilient. Due to differing sociocultural contexts, the resilience perceptions of communities in different parts of the world may vary. This study aims to understand community resilience factors after the COVID-19 disaster in Indonesia and Malaysia. Data from 2034 questionnaires using 5-interrelated domains in the Communities Advancing Resilience (CART) Toolkit Survey were collected. This study was conducted across Indonesia and Malaysia from March to April 2022. A quantitative-based cross-sectional study design and convenience sampling were applied. Respondents for this study were Indonesian and Malaysian citizens above 18 years of age who met the inclusion criteria. A total of 2034 respondents, 715 from Indonesia and 1315 from Malaysia responded to the survey. The results suggest that Indonesian and Malaysian communities’ Transformative Potential and Informative-Communication domains differ significantly. Indonesian communities demonstrated a higher mean value on Transformative Potential domains than Malaysian communities did, while Malaysian communities indicated a higher mean value on Informative-Communication domains. This study concludes that compared to Malaysian communities, Indonesian communities have a more significant potential for transformation because they can frame collective experiences, gather, and analyze pertinent data, evaluate community performance, and develop resilience-building abilities. On the other hand, Malaysian communities are more resilient in providing information and communication. We found the need to develop a community resilience model that incorporates specific cultural and local requirements. Cooperation between the two countries would open many possibilities to emphasize the capability to bounce back sooner after a catastrophe such as the COVID-19 pandemic and achieve Sustainable Development Goals.